Triggers of Consumer Impulse Buying Behavior on E-Commerce Platforms: A Systematic Literature Review - Thamara, Shely Dinar; Syarif, Muhammad; Suyono, Suyono (PT FORMOSA CENDEKIA GLOBAL, 2025)
The development of digital technology has brought about significant changes in consumer shopping habits, particularly with the increasing use of e-commerce platforms. One interesting phenomenon that has emerged is impulsive buying behavior, namely the decision to purchase a product suddenly without planning. This study aims to identify factors that influence this behavior using the Systematic Literature Review (SLR) method. A total of seven relevant scientific journals were reviewed in depth to understand consistent patterns and findings across various studies. The analysis results show that impulsive buying is influenced by a combination of various factors such as the attractive visual appearance of the platform, ease of use of the technology, social influence from others, and positive emotions experienced by consumers while shopping. This study also uses several major theoretical approaches, such as Stimulus-Organism-Response (SOR), Theory of Planned Behavior (TPB), Technology Acceptance Model (TAM), and Expectation Confirmation Theory (ECT). These findings indicate that consumer behavior in e-commerce is not only determined by rational needs, but also by emotional and social experiences shaped by digital technology. Therefore, businesses need to create an attractive, convenient, and personalized shopping experience to encourage purchasing decisions.